Assessing the Adoption and Impact of Industry 4.0 Technologies in Oil and Gas EPC Companies: A Survey- Based Study on Operational Efficiency and Cost Management - Kumar, Vijaya (MultiTech Publisher, 2024)
This research paper conducts a comprehensive survey on the adoption of Green Project Management (GPM) principles across various industries in India, aiming to understand the extent and impact of these practices. The study's primary objective is to evaluate the awareness, implementation and challenges of GPM in different sector, and how these factors correlate with the industry characteristics and professional experience. Methodologically, the research employed a structured questionnaire distributed to 1200 participants across major industrial regions in India, followed by a meticulous analysis using statistical tools like ANOVA and Chi-Square tests. Key findings reveal significant variations in the awareness and adoption of GPM principles among different industries, with sectors such as IT and energy demonstrating higher levels of implementation. A notable correlation was observed between professional experience and the adoption of GPM practices, indicating a maturity curve in GPM integration. Additionally, the study highlighted industry-specific challenges and benefits, underscoring the need for tailored approaches in promoting GPM. The implications of these findings are profound, suggesting the necessity for targeted educational initiatives and policy interventions to enhance GPM adoption. It emphasizes the role of industry-specific strategies and the importance of professional development in integrating sustainability into project management practices. This study contributes to the ongoing discourse on sustainable development, offering valuable insights for industry leaders, policymakers, and academia in strategizing GPM's effective integration